A perspective on the impact of the Deposit Taking Institutions Act on banks in South Africa - Jacobson, Ari Hugh (School of Economics, 2016)
The primary objective of this mini-thesis is to show that the new banking legislation, which was implemented in South Africa in February 1991, as the Deposit Taking Institutions Act of 1990 [hereinafter "DTl"], encouraged the trend towards larger financial institutions in South Africa. A further aim of this thesis is to find a variable that best represents a financial institution's performance and to use this measure to determine a relationship, if any, with an individual bank's size. The test is to be conducted utilising a sample of South African banking institutions. The concept of size versus performance has been considered often in myriad studies of financial institutions worldwide. However, it should be noted that studies regarding the performance of the banking industry in South Africa, are virtually non-existent. In Chapter 1, a brief history of world banking trends will be discussed, while in Chapter 2 we will deal with bank developments in South Africa, including an in-depth study of the DTI Act. In Chapter three, we survey banking literature and note particularly the methodologies employed in analysing the relevance of performance indicators, and the criterion used, to demonstrate the effectiveness and efficiency of a financial institution. It is shown that at least fifty studies, between 1990 and 1993 have purported to demonstrate, inter a/ia, the influence of government regulation on banking performance, economies of scale at banks, benefits associated with interbank mergers, as well as the results of bank and non-bank mergers. Contemporary studies of the banking industry have also employed a variety of measurement techniques to evaluate a bank's performance. This has entailed various approaches ranging from fundamental analysis to more sophisticated programming methodologies. Moreover research has attempted to discern the optimal level of efficiency, at an individual financial institution. The underlying objective of this mini-thesis is to reveal whether big banks perform better than small banks in South Africa. Here it is hypothesised that legislation, in the form of the DTI Act, has in fact given rise to bigger banks. Yet there is evidence, [Boyd and Runkle(1993)], that bigger banks are not better performing banks. Following in part from Boyd and Runkle, the performance criterion to be used, herein, is the price earnings (PE) ratio, while size is determined by gross advances. The aim of this enquiry is to look at an individual bank to gauge a relationship, if any, between size and performance. The expectation is that the bigger the bank the higher its PE ratio, because there is clear support for bigger banks in the DTI Act, as will be argued in Chapter 2 & 4.